1993
DOI: 10.1002/1097-0142(19930315)71:6<2105::aid-cncr2820710627>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Cranial computed tomography in children with acute lymphoblastic leukemia after prophylactic treatment with cranial radiation therapy and intrathecal methotrexate

Abstract: Background and Methods. Thirty‐one children with acute lymphoblastic leukemia (ALL) who had received cranial radiation therapy (Cr RT) and five concomitant doses of intrathecal methotrexate (IT MTX) for central nervous system prophylaxis (CNSP) and who had an event‐free survival exceeding 5 years had cranial computed tomography (Cr CT) examination. The fractional dose for 21 of them was 1.5 Gy. The interval between the completion of CNSP and the time of Cr CT ranged from 5 to 8.5 years, with a median of 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Dexamethasone, a major cyclic component during the maintenance phase, has also made an important contribution to the prevention of CNS relapse, as has been addressed in the Children's Cancer Group [10] and Dutch Childhood Leukemia Study Group [11]. We have previously reported that no patients with such CNS prophylaxis had cranial computed tomography abnormalities [12], and their IQ scores all fell within the average range during a 5-year follow-up [13]. However, longer follow-up is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone, a major cyclic component during the maintenance phase, has also made an important contribution to the prevention of CNS relapse, as has been addressed in the Children's Cancer Group [10] and Dutch Childhood Leukemia Study Group [11]. We have previously reported that no patients with such CNS prophylaxis had cranial computed tomography abnormalities [12], and their IQ scores all fell within the average range during a 5-year follow-up [13]. However, longer follow-up is mandatory.…”
Section: Discussionmentioning
confidence: 99%